2004
DOI: 10.1038/ni1129
|View full text |Cite
|
Sign up to set email alerts
|

Cognate CD4+ T cell licensing of dendritic cells in CD8+ T cell immunity

Abstract: Several studies have indicated that CD8(+) T cells require CD4(+) T cell help for memory formation. Evidence suggests that such help can be antigen independent, challenging whether the 'licensing' of dendritic cells (DCs) by CD4(+) T cells is ever required for cytotoxic T lymphocyte (CTL) responses. We show here that help is essential for the generation of CTL immunity to herpes simplex virus 1 and that CD4(+) T cells mediate help in a cognate, antigen-specific way. We provide direct in vivo evidence for DC li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
313
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(330 citation statements)
references
References 40 publications
12
313
1
4
Order By: Relevance
“…DC licensing by T helper cells is a well-accepted phenomenon that is crucial for effective CD81 T cell immunity (52,53). DC conditioning requires cognate interaction between CD41 T cells and DCs, is dependent on costimulatory signals, and is crucial for both effector and memory CD81 T cell responses (52,54). In our system, this could be due to either inhibition of secondary costimulatory pathways, such as CD40/CD40L, or inhibition of T cell effector cytokine production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DC licensing by T helper cells is a well-accepted phenomenon that is crucial for effective CD81 T cell immunity (52,53). DC conditioning requires cognate interaction between CD41 T cells and DCs, is dependent on costimulatory signals, and is crucial for both effector and memory CD81 T cell responses (52,54). In our system, this could be due to either inhibition of secondary costimulatory pathways, such as CD40/CD40L, or inhibition of T cell effector cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding demonstrating an alternative mode of action of abatacept in which inhibition of T cell activation leads to a modulation of the function of APCs. DC licensing by T helper cells is a well-accepted phenomenon that is crucial for effective CD81 T cell immunity (52,53). DC conditioning requires cognate interaction between CD41 T cells and DCs, is dependent on costimulatory signals, and is crucial for both effector and memory CD81 T cell responses (52,54).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CD8 1 T cells may be ''tolerized'' readily without providing substantial feedback signals to DC. In contrast, activated and memory CD4 1 T cells could provide activation signals to DC through, for instance, CD40/ CD40L interactions [41] and promote DC activation [42][43][44] thereby limiting the ability of the DC to induce peripheral tolerance. Indeed, we and others have shown previously that coactivation of cognate CD4 1 T-cell help impairs tolerance induction, but for antigen transgenically targeted to DC this effect is transient [13].…”
Section: Discussionmentioning
confidence: 99%
“…Many new adjuvants are currently in development, some of which exploit pathogen-associated molecular patterns with formulations that include TLR ligands. Adjuvants, however, are not always sufficient for immunogenic CTL priming, as signals from CD4 + T helper cells are also required [3,[8][9][10]. Thus, optimal CTL priming by DC includes induction of costimulatory signals and efficient antigen presentation to both CD4 + and CD8 + T cells.…”
mentioning
confidence: 99%
“…The authors observed that more CD11c-targeted antigen reached the spleen than that directed towards CD205 [19]. This is important, because cross-priming of soluble antigen mostly occurs in the spleen [4,10]; however, this cannot be the whole explanation, because MHC II-targeting also efficiently delivered antigen to the spleen, yet was far less effective at CTL generation [19]. This theoretically might be explained by antigen delivery to splenic B cells, which express MHC II, but no CD11c, and are known to tolerize CTL, at least in their resting state [24].…”
mentioning
confidence: 99%